Clientelism or Something Else? Squatter Politics in Montevideo (2012)
Through the in-depth ethnographic study of one squatter neighborhood in Montevideo and its leader's political networks, this article illustrates a successful strategy through which some squatter neighborhoods have fought for their right to the city. This consists of opportunistic, face-to-face relationships between squatter leaders and politicians of various factions and parties as intermediaries to get state goods, such as water, building materials, electricity, roads, and ultimately land tenure. Through this mechanism, squatters have seized political opportunities at the national and municipal levels. These opportunities were particularly high between 1989 and 2004, years of great competition for the votes of the urban poor on the periphery of the city, when the national and municipal governments belonged to opposing parties. In terms of theory, the article discusses current literature on clientelism, posing problems that make it difficult to characterize the political networks observed among squatters. © 2012 University of Miami.